Strategic Implementation of Social Inclusion-Based Library Transformation - Firly Erya Faldilal Nuraini; Agus Widiyarta Widiyarta (Jurnal Kebijakan Publik, 2025)
This study examines the strategic implementation of the Social Inclusion-Based Library Transformation (TPBIS) by the East Java Provincial Library and Archives Office. A descriptive qualitative method was employed, using Fred R. David's strategic implementation theory as an analytical framework, focusing on three key aspects: annual objectives, basic policies, and resource allocation. The findings indicate that TPBIS annual objectives are formulated based on national policy directives and localized through internal discussions and regional development plans. These objectives emphasize improving library services and delivering community-based training programs to empower marginalized groups such as people with disabilities and informal workers. Basic policies are supported through internal regulations, certified staff training, and the formation of implementation teams. In terms of resources, TPBIS is funded by the regional budget (APBD) and supplemented by CSR partnerships. It is implemented by trained personnel and supported by physical infrastructure including Graha Pustaka, inclusive reading spaces, and skill-training incubators. Despite these efforts, the program still faces challenges, particularly related to limited funding, infrastructure, and low community participation. Therefore, the success of TPBIS requires continuous innovation, sustainable mentoring systems, and strengthened cross-sector advocacy. This case study highlights the importance of aligning strategic goals with community needs and improving public engagement to optimize the transformation of libraries into inclusive, empowering institutions. The results are expected to provide insights for strengthening the strategic implementation of TPBIS in other regions.